DETERMINAN KINERJA MANAJERIAL PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN ACEH TAMIANG - Afriza; Nurlaila Hanum; Muhammad Salman (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2021)
This study aims to determine the effect of budgetary participation, clarity of budget tergets, and psycological capital on manajerial performance in the regional work unit of Aceh Tamiang regency. The population of this research is all regional work units in Aceh Tamiang regency as many as 32. The sampling technicue used in this study was a saturated sample (census sample). Data collection was done by distributing questionnaires to 96 respondents. the data obtained is then analyzed using SPSS using data analysis techniques (validity and reliability test, classical assumption test, multiple linear regression tests and hypothesis testing). Based on the research objectives, the results showed that partially the variables of budgetary participation and clarity of budget targets had a significant influence on managerial performance. While the psychological capital variable has a positive but not significant effect on managerial performance. Meanwhile simultaneously. The variables of budgetary participation, clarity of budget targets, and psychological capital have a significant influence on managerial performance.